Email ethics for authors: From the world of publication process - Subrata, Sumarno Adi (Universitas Muhammadiyah Magelang, 2025)
The publication process relies heavily on email communication among authors, editors, and reviewers. However, the informal nature of email can lead to breaches of ethics that compromising the integrity of the publication process. This editorial examines the ethical considerations surrounding email communication in publication, including confidentiality, tone, and content. The article discusses the importance of maintaining confidentiality and avoiding conflicts of interest, as well as the need for clear and respectful communication. Furthermore, this work explores the role of email in peer review, editorial decision-making, and author-editor communication and highlight potential pitfalls and best practices. Establishing guidelines for email ethics can promote transparency, accountability, and professionalism in the publication process. It also can enhance the credibility and reliability of published research in research. Along with that, this editorial provided discussion and guide stakeholders in directing the complexities of email communication. In the context of publishing innovations in health, email communication serves to facilitate collaboration, peer review, and editorial decision-making. For instance, when submitting a manuscript to a health innovation journal, authors rely on email to communicate with editors and reviewers. A breach of confidentiality or unprofessional tone in these interactions can undermine the integrity of the publication process and potentially delay or jeopardize publication. In health innovation research, the accuracy and reliability of findings are crucial for public health policy and practice. Keywords: Academic publication; journal editor; scientific contribution; healthcare science; role models